2023
DOI: 10.3390/ijerph20021307
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Metabolic Syndrome and Its Components in Latino Immigrants to the USA

Abstract: The Metabolic Syndrome (MetS) is an increasingly prevalent condition globally. Latino populations in the USA have shown an alarming increase in factors associated with MetS in recent years. The objective of the present systematic review was to determine the prevalence of MetS and its risk factors in immigrant Latinos in the USA and perform a meta-analysis of those prevalence. The review included cross-sectional, cohort, or case–control studies involving adult immigrant Latinos in the USA, published during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The HOMA-IR index (p < 0.001) also showed a positive association with liver disease. 10 The results of this study demonstrated the relationship between NASH and a set of risk factors that represent a complex disorder of modern civilization, MS. 5 Therefore, MS was associated with NASH through the following variables: positive diagnosis of type 2 DM, presence of obesity, high serum levels of glucose and insulin, high HDL-c, waist circumference with high adipose tissue, individuals conditioned individuals with high blood pressure and high HOMA-IR index scores. 6,7 Moreover, when risk factors are positive and increased, they are also indicators of more advanced degrees of fibrosis.…”
Section: Resultsmentioning
confidence: 62%
“…The HOMA-IR index (p < 0.001) also showed a positive association with liver disease. 10 The results of this study demonstrated the relationship between NASH and a set of risk factors that represent a complex disorder of modern civilization, MS. 5 Therefore, MS was associated with NASH through the following variables: positive diagnosis of type 2 DM, presence of obesity, high serum levels of glucose and insulin, high HDL-c, waist circumference with high adipose tissue, individuals conditioned individuals with high blood pressure and high HOMA-IR index scores. 6,7 Moreover, when risk factors are positive and increased, they are also indicators of more advanced degrees of fibrosis.…”
Section: Resultsmentioning
confidence: 62%
“…In a recently published meta-analysis from ( 11 ), 52 studies with 436,654 immigrant Latinos in the United States reported a pooled prevalence for arterial hypertension of 28% (95% confidence intervals (CIs): 23–33%), type 2 diabetes mellitus of 17% (95% CIs: 14–20%), general obesity of 37% (95% CIs: 33–40%), and abdominal obesity of 54% (95% CIs: 48–59%) ( 11 ). The obtained results from our participants were as follows: The prevalence of arterial hypertension was 8.8%, type 2 diabetes mellitus was 4.6%, and general obesity was 10.7%.…”
Section: Discussionmentioning
confidence: 99%
“…According to data from the United States census ( 10 ), the Latin population reached a total of 62.5 million people in 2021, which shows a 19% increase from the 50.5 million of Latinos in 2010. Therefore, there is a high prevalence of general obesity among Latin immigrants ( 11 ).…”
Section: Introductionmentioning
confidence: 99%